Breast Milk Production in terms of Knowledge of Postpartum Mother about the Initiation of Early Breastfeeding in Newborns - Patonah, Siti; Susanti, Dwi Agung; Anggraita, Dara Dwifa (Universitas STRADA Indonesia, 2019)
Background: Many mothers do not know about the benefits of Breast Crawl. Often mothers have an improper understanding, such as not having to breastfeed the baby because the breast milk has not come out or because the milk that comes out first and yellow is the dirt and stale.Purpose: The purpose of this research is to know the relationship of postpartum knowledge about Breast Crawl in newborn with the smoothness of milk production.Method: This research use analytical method with cross sectional approach. The study was conducted on May 29 to June 23, 2018. The population in this study were all post partum mothers in Sri Widayati Wiwik BPS, SST Tanggungan Ngraho Sub-district Bojonegoro Regency in 2018 as many as 22 people, the sample size of 22 postpartum women was taken by purposive sampling technique. The instrument used is a questionnaire, then performed data processing through editing, coding, scoring and tabulating and analysis of data with Cross tables.Results: The results showed that 22 postpartum mothers in BPS Wiwik Sri Widayati, SST Tanggungan Ngraho Sub-district Bojonegoro Regency is knowledgeable good of 11 people, more than half the smoothness of breast milk production smoothly for 14 people (63,64%).Conclusion: There is relation of maternal knowledge about Breast Crawl on newborn with smoothness of breast milk production at BPS Wiwik Sri Widayati, SST Tanggungan Ngraho Sub-district Bojonegoro Regency. From the results of this study should postpartum mother can improve knowledge especially about Breast Crawl in newborn by coming to counseling conducted by health workers at Maternal & Child Health Centre every month